2017
DOI: 10.13040/ijpsr.0975-8232.8(3).1048-55
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Diabetes poses a burden on the limited health care delivery system. Current pharmacological anti-diabetic agents cause undesirable side effects and are very expensive. Herbal remedies offer the potential for alternative treatment strategies. This study was therefore conducted in an effort to formulate a poly herbal medicine for management of diabetes. Methods: A stenophylla root bark was extracted with aqueous ethanol (70%) and quantitative analysis for total phenolic content, total alkaloids and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…and 50% lemon juice (L.J.). This exact formulation was due to the mixture of ginger and lemon juices and also due to studies previously done on the formulation containing Zingiber officinale and Citrus limon with different biological effects. …”
Section: Methodsmentioning
confidence: 99%
“…and 50% lemon juice (L.J.). This exact formulation was due to the mixture of ginger and lemon juices and also due to studies previously done on the formulation containing Zingiber officinale and Citrus limon with different biological effects. …”
Section: Methodsmentioning
confidence: 99%
“…ex Benth peel flour formulated biscuits have improved total phenolic and flavonoid content as well as antioxidant activity (Ramashia et al, 2021). (Verengai et al, 2017) and increase in glucose uptake was observed in C2C12 myocytes treated with ethanolic extracts (Taderera et al, 2019).…”
Section: The Parinari Curatellifoliamentioning
confidence: 99%
“…The roots have been used as antidotes and snake repellents ( Maroyi, 2019 ). ( Verengai et al, 2017 ) studied the effects of ethanolic extracts of Annona stenophylla Engl. and Diels on alloxan-induced diabetic rats, and observed a dose dependent decrease of plasma glucose levels of the diabetic rats.…”
Section: Medicinal Plants In Zimbabwe With Antidiabetic Propertiesmentioning
confidence: 99%